2009
DOI: 10.1097/hnp.0b013e3181a056c4
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Nurses' and Midwives' Academic/Clinical Workplaces

Abstract: This article reveals the findings from a recent international ethnographic research project on nurses' and midwives' resilience, hope, and optimism in their workplace. The research found that the need for resilience was critical to one's healing in the workplace. An innovative model to respond strategically to the workplace is revealed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 34 publications
0
40
0
Order By: Relevance
“…Given the need identified in the literature for healthcare staff to be resilient (Glass, 2009), benefit may be gained from more explicit pre-placement preparation, to help students develop strategies to better support their mental health when confronted with the challenges of practice. Supporting previous In particular, placement was highlighted as being potentially problematic for the mental well-being of some students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the need identified in the literature for healthcare staff to be resilient (Glass, 2009), benefit may be gained from more explicit pre-placement preparation, to help students develop strategies to better support their mental health when confronted with the challenges of practice. Supporting previous In particular, placement was highlighted as being potentially problematic for the mental well-being of some students.…”
Section: Discussionmentioning
confidence: 99%
“…Not only might the realities of clinical placement put student mental health under stress, curriculum content can challenge personal beliefs and generate levels of cognitive dissonance that create additional psychological distress (Stephens, 2013;Thomas & Asselin, 2018;Thomas & Revell, 2016). Glass (2009), for instance, has shown that resilience is a necessary quality in everyday nursing practice. Glass (2009), for instance, has shown that resilience is a necessary quality in everyday nursing practice.…”
mentioning
confidence: 99%
“…Others have taken an ethnographic approach (e.g. Glass 2009). Research on burnout in midwifery can also shed light on the factors which may be linked with burnout or protect against it, thereby sustaining practitioners (Yoshida & Sandall, 2013;Young, Smythe, & McAra Couper, 2015).…”
Section: Applying Sustainability and Resilience To Midwiferymentioning
confidence: 99%
“…Workplace environments characterized by high job demands, intensity in care delivery, job burnout, and loss of staff due to health issues, have resulted in a continuum of health disruption for practitioners 1,2…”
Section: Introductionmentioning
confidence: 99%